2004
DOI: 10.1023/b:egah.0000039592.80489.e5
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Benzo[a]Pyrene in Soil with Arbuscular Mycorrhizal Alfalfa

Abstract: Mycorrhizal and non-mycorrhizal alfalfa (Medicago sativa) was grown in pots containing soil artificially contaminated with various levels of benzo[a]pyrene (B[a]P) (0, 1, 10 and 100 mg kg )1 ). Soil and plants were sampled after 30, 40, 50, 60 and 90 days and compared with unlanted pots. The percentage of mycorrhizal root length colonized by Glomus caledoniun was not significantly affected by the addition of B[a]P up to 10 mg kg )1 but was significantly lower at 100 mg kg )1 B[a]P compared with low concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 30 publications
3
23
0
5
Order By: Relevance
“…A drastic negative phenanthrene effect on the mycorrhization of ryegrass and red clover was quantified. Similar results have been found in several studies such as the negative benzo(a)pyrene effect on the alfalfa mycorrhization (Liu et al 2004). On the contrary, the colonisation of red clover by Rhizobium was stimulated by the presence of phenanthrene.…”
Section: Discussionsupporting
confidence: 91%
“…A drastic negative phenanthrene effect on the mycorrhization of ryegrass and red clover was quantified. Similar results have been found in several studies such as the negative benzo(a)pyrene effect on the alfalfa mycorrhization (Liu et al 2004). On the contrary, the colonisation of red clover by Rhizobium was stimulated by the presence of phenanthrene.…”
Section: Discussionsupporting
confidence: 91%
“…Parrish et al (2004) reported 24% dissipation of total PAHs in composted soil in the presence of tall fescue. Greenhouse experiments have demonstrated enhanced removal of PAHs when alfalfa was planted compared with unplanted controls (Liu et al 2004). These results were obtained using single plant species and little is known about how plant species and cropping patterns affect the processes by which phytoremediation removes PAHs on a field scale (Meng et al 2011;Wei and Pan 2010).…”
Section: Introductionmentioning
confidence: 61%
“…Phytoremediation, the use of plants to remediate contaminated soil, has been described as a promising approach to remediate soils contaminated with persistent organic pollutants such as PAHs (Chen et al 2003;Huang et al 2004;Phillips et al 2009). During the last few decades, numerous plant species including alfalfa and tall fescue have been found to be promising candidates for phytoremediation of PAHs (Liu et al 2004;Parrish et al 2004;Balcom and Crowley 2009). Parrish et al (2004) reported 24% dissipation of total PAHs in composted soil in the presence of tall fescue.…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that PW inoculation was the main reason increased the activity of polyphenol oxidase. And the enhanced polyphenol oxidase activity in RP treatment may contribute to the increasing dissipation of pyrene as polyphenol oxidase can catalyze the degradation and transformation of aromatic compounds (Gramss et al, 1999;Liu et al, 2004). Thus, microbial degradation appears to be the most important approach during the remediation process and plant growth will in turn enhance the microbial growth of both native and introduced strains.…”
Section: Effect Of Bioaugmentation On Soil Enzyme Activitiesmentioning
confidence: 99%